Characterization and optimization of 1-Aminocyclopropane-1-Carboxylate Deaminase (ACCD) activity in different rhizospheric PGPR along with Microbacterium sp. strain ECI-12A - Shrivastava, Umesh P.; Kumar, Ashok (International Journal of Applied Sciences and Biotechnology, 2013)
A total of nine strains of plant growth promoting rhizobacteria were analyzed for ACC deaminase activity, where highest ACC deaminase activity was found in Klebsiella sp strain ECI-10A (539.1 nmol α-keto butyrate/ mg protein/ h) and lowest in Microbacterium sp strain ECI-12A (122.0 nmol α-keto butyrate/ mg protein/ h). Although Microbacterium sp strain ECI-12A showed lowest level of ACC deaminase activity, but, the species of Microbacterium isolated from rhizosphere is the first report. Microbacterium sp strain ECI-12A was also analyzed under varying conditions of time, amount of 1-Aminocyclopropane-1- carboxylate (ACC), and temperature for optimization of the ACC deaminase activity. The optimum activity was recorded with the supplementation of 5mM ACC at 30°C temperature after 24h of culture growth. All the nine strains showed acdS gene in the PCR amplification of that gene. No any rhizospheric Microbacterium species showing ACC deaminase activity have been reported earlier, therefore, we report here ACC deaminase activity in Microbacterium sp ECI-12A isolated from rice rhizosphere is a novel finding. DOI: http://dx.doi.org/10.3126/ijasbt.v1i1.7921 Int J Appl Sci Biotechnol, 2013, Vol. 1(1): 11-15